Baliwag Sports and Recreational Complex encouraging physical activity through architecture - Chua, Jaime Vincent R.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This project is created out of a need to address the prevalence of overweight and underweight individuals, under appreciation of physical activity, and a lack of open spaces. The concurrence of these problems creates an escalating problems of health deterioration that should not be allowed to progress any further. In order to address these, the designer resolved to create a project that allows people to invest in their personal competencies using physical activity as the catalyst. This project serves as a framework by which to combat the debilitating effects of the issues and create health and wellness for people of all ages, shapes, and sizes. Located in Bulacan, the Baliwag Sports and Recreational Complex is fashioned out of the connections between physical activity and the different forms of wellness. The outcome is a health-promoting, inclusive, and culturally-integrated facility designed to enrich the local community by providing a supportive and accessible environment for all manner of sports/exercise programs, social interaction and professional instruction.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Health and Wellness Facility -- Design